(untitled) (Eurasian Journal of Ecology, 2022)
Microalgae are characterized by rapid photoautotrophic growth and a high rate of biomass accumulation and are considered as an alternative feedstock for renewable energy sources such as biodiesel. Biofuel research is not just a matter of finding the right type of biomass and converting it into fuel, but also finding environmentally and economically viable options. The paper presents the results of studies on the use of thermal and mineral water sources as a medium for the cultivation of microalgae Parachlorella kessleri DZP-5, Parachlorella kessleri B2 and Ankistrodesmus falcatus B5. It was shown that when using water from the «Arshan» thermal water source and the Balkhash salt lake to dilute the Tamiya medium in a ratio of 50:50, it is possible to obtain an intensive growth of microalgae cultures and at the same time preserve the main characteristics of microalgae producers of biodiesel fuel. The composition of fatty acids of three tested strains of microalgae is also given, which showed their potential as producers of biodiesel. Key words: microalgae, thermal and mineral springs, cultivation, biodiesel producers, fatty acids.